2019
DOI: 10.1152/ajpheart.00188.2019
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA LINC00342 promotes growth of infantile hemangioma by sponging miR-3619-5p from HDGF

Abstract: Infantile hemangiomas (IH) are a type of benign vascular neoplasm that may cause permanent scarring. Hemangioma-derived endothelial cells (HemECs) are commonly used as an in vitro model to study IH. Long noncoding RNA is a type of RNA transcript longer than 200 nucleotides that does not encode any protein. LINC00342 was discovered to regulate proliferation and apoptosis in nonsmall cell lung cancer. However, the role of LINC00342 in IH has never been reported before. Expressions of LINC00342 and miR-3619-5p we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 36 publications
0
16
1
Order By: Relevance
“…In addition, we found that linc-ROR could function as a ceRNA sponge for miR-194-3p, miR-3164, miR-3619-5p, miR-491-5p, and miR-5001-5p. Among these five miRNAs, miR-3164 was found to participate in the ceRNA mechanism of circRAD18 to promote tumor progression in triple-negative breast cancer (Zou et al, 2019); miR-3619-5p was reported to be involved in the ceRNA regulatory networks of linc01410 in papillary thyroid carcinoma (Wang et al, 2019), linc00342 in infantile hemangioma (Liu et al, 2019), linc00202 in retinoblastoma (Yan et al, 2019), and circZFR in hepatocellular carcinoma ; miR-491-5p was found to be an inhibitor both in ERa-positive breast cancer (Hui et al, 2015) and in HER2-positive breast cancer cells (Leivonen et al, 2014). There were limited studies about miR-5001-5p in breast cancer.…”
Section: Linc-ror Promotes Cell Proliferation Migration and Invasiomentioning
confidence: 99%
“…In addition, we found that linc-ROR could function as a ceRNA sponge for miR-194-3p, miR-3164, miR-3619-5p, miR-491-5p, and miR-5001-5p. Among these five miRNAs, miR-3164 was found to participate in the ceRNA mechanism of circRAD18 to promote tumor progression in triple-negative breast cancer (Zou et al, 2019); miR-3619-5p was reported to be involved in the ceRNA regulatory networks of linc01410 in papillary thyroid carcinoma (Wang et al, 2019), linc00342 in infantile hemangioma (Liu et al, 2019), linc00202 in retinoblastoma (Yan et al, 2019), and circZFR in hepatocellular carcinoma ; miR-491-5p was found to be an inhibitor both in ERa-positive breast cancer (Hui et al, 2015) and in HER2-positive breast cancer cells (Leivonen et al, 2014). There were limited studies about miR-5001-5p in breast cancer.…”
Section: Linc-ror Promotes Cell Proliferation Migration and Invasiomentioning
confidence: 99%
“…Accumulating evidence indicates that lncRNAs play a crucial role in human diseases, especially in various cancers. [17][18][19][20][21][22][23][24][25][26][27][28] LncRNAs participate in almost all cellular sh-TP-53, sh-ESR1, and sh-NC. D, DDX3 and YY1 coimmunoprecipitation and western blot assay were conducted in DLD-1 cells, which transfected the overexpression of TCONS_00012883 and controls.…”
Section: Discussionmentioning
confidence: 99%
“…LINC00342, a novel lncRNA located on chromosome 2q11.1, is up-regulated in non-small cell lung cancer (NSCLC) and infantile hemangiomas [24,25]. High expression of LINC00342 predicts a poor prognosis in NSCLC [26].…”
Section: Discussionmentioning
confidence: 99%